ISNAR Annual Report 2002 - International Service for National Agricultural Research (International Service for National Agricultural Research, 2003)
It is unlikely that the United Nations' Millennium Goal to halve poverty and food insecurity by 2015 will be reached. In the 2002 Annual Report, ISNAR's Director General, Stein W. Bie, argues that the world can only hope to reduce hunger, produce food sustainably, and alleviate poverty if it takes investments in the rural sector in developing countries seriously. He explains how ISNAR's Road Map 2002-2006 plots a course for institutional innovation as the backbone of rural poverty eradication. This Annual Report also provides a brief update on some of the exciting changes we have introduced on our website in 2002 (see page 20), and it also includes a CD-ROM with all of ISNAR's publications produced since 1995-a virtual library of global public goods that will help those who have no Internet connection to access ISNAR's electronic publications, including ISNAR's new Road Map.